2011
DOI: 10.1016/j.bandl.2011.05.006
|View full text |Cite
|
Sign up to set email alerts
|

The organization of narrative discourse in Lewy body spectrum disorder

Abstract: Narrative discourse is an essential component of day-to-day communication, but little is known about narrative in Lewy Body spectrum disorder (LBSD), including Parkinson's disease (PD), Parkinson's disease with dementia (PDD), and dementia with Lewy bodies (DLB). We performed a detailed analysis of a semi-structured speech sample in 32 non-aphasic patients with LBSD, and we related their narrative impairments to gray matter (GM) atrophy using voxel-based morphometry. We found that patients with PDD and DLB hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 71 publications
(100 reference statements)
8
82
0
Order By: Relevance
“…In Parkinson's disease (PD) and early Alzheimer's disease, researchers have found that individual word comprehension is relatively intact, yet the ability to infer the meaning of the text is impaired (44). In PD, this deficit in the organization and interpretation of narrative discourse was associated with reduced cortical volume in several brain regions, including the superior part of the left STS and the anterior cingulate (45). Our finding that these regions demonstrated large differences between the stories (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In Parkinson's disease (PD) and early Alzheimer's disease, researchers have found that individual word comprehension is relatively intact, yet the ability to infer the meaning of the text is impaired (44). In PD, this deficit in the organization and interpretation of narrative discourse was associated with reduced cortical volume in several brain regions, including the superior part of the left STS and the anterior cingulate (45). Our finding that these regions demonstrated large differences between the stories (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The narrative abilities of focal neurodegenerative disease patients have previously been compared in controlled, experimental studies (Ash et al, 2011; Ash et al, 2006; Chapman et al, 2005; Farag et al, 2010); however, this is the first study to quantify narrative production of neurodegenerative disease groups in the form of storytelling in a naturalistic social interaction and to compare patterns of neurodegeneration with specific narrative devices such as narrative evaluations, oft-cited as the most important aspect of storytelling and which reflect key inferential and valuation processes inherent to personal narratives.…”
Section: Discussionmentioning
confidence: 99%
“…The few discourse studies to date report a trend toward decreased informational content as well as decreased complexity of syntax [4][5][6]. Others report no abnormalities with narrative production in non-demented individuals with PD [7]. These observations are difficult to interpret due to the limited and variable nature of studies to date.…”
Section: Introductionmentioning
confidence: 61%
“…The exception is a study by Ash and colleagues [7] which found no significant impairments of narrative discourse in a group of 18 nondemented, individuals with PD; however, all participants were medicated when providing their narrative discourse sample. Other investigators [4,5] did not examine cohesion/coherence, but did find deficits in discourse-level information content in individuals with PD.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation